Experimental and first-principles investigation on the structural, electronic and antimicrobial properties of nickel hydroxide nanoparticles. (January 2022) - Chaudhari, Vilas P.; Rajput, Kaptan; Mondal Roy, Sutapa; Chaudhuri, Tapas K.; Roy, Debesh R.
Abstract: The present work reports a detailed and joint experimental and first-principles theoretical investigation on the structural and electronic properties and antimicrobial activity of nickel hydroxide [Ni(OH)2 ] nanoparticles (NPs) synthesized using a hydrothermal method. We demonstrate the first attempt to determine the antimicrobial effect of Ni(OH)2 NPs on Gram-negative and Gram-positive bacteria, in terms of minimum inhibitory concentration (MIC) and zone of inhibition (ZOI). The Ni(OH)2 NPs were synthesized by hydrothermal method using a Teflon-lined stainless-steel autoclave. The synthesized NPs were characterized using X-ray diffraction (XRD), UV–visible spectroscopy and transmission electron microscopy (TEM). The TEM analysis shows that the average size of the synthesized NPs is 1–3 nm. Density functional calculations are also carried out to understand and confirm the structural and electronic properties of synthesized NPs. Antibacterial activity of Ni(OH)2 NPs is tested against two different types of bacteria – Bacillus subtilis (Gram-positive) and Escherichia coli (Gram-negative) – using the well diffusion method, in terms of MIC and ZOI. Our synthesized Ni(OH)2 NPs show significant antibacterial activity against both B. subtilis and E. coli . The antibacterial activity increases with the increase in Ni(OH)2 NP concentration, measured as ZOI of Ni(OH)2 NPs, which may contribute significantly to possible medicinal applications of Ni(OH)2 NPs. Graphical abstract: Image 1 Highlights: Ni(OH)2 nanoparticles (NPs) of 1–3 nm synthesized by hydrothermal method. Ni(OH)2 NPs are characterized through XRD, UV–Vis spectroscopy and TEM techniques. Structural and electronic properties of Ni(OH)2 NPs analyzed using DFT calculations. Antimicrobial studies of Ni(OH)2 NPs are performed in terms of MIC and ZOI. Ni(OH)2 NPs show remarkable promise for relevant medicinal applications.